Crystal structure of (2-methyl-4-phenyl-4H-benzo[4,5]thiazolo[3,2-a]pyrimidin-3-yl)(phenyl)methanone - Sankar, T. (Acta Crystallogr E Crystallogr Commun, 2015)
In the title compound, C(24)H(18)N(2)OS, the pyrimidine ring has a flat envelope conformation with the methine C atom as the flap. The attached phenyl and benzoyl rings are inclined to the mean plane of the pyrimidine ring by 84.87 (8) and 75.33 (9)°, respectively. The benzothiazolo group is planar (r.m.s. deviation = 0.009 Å) and inclined to the mean plane of the pyrimidine ring by 3.27 (6)°. In the crystal, molecules are linked by pairs of C—H⋯N hydrogen bonds, forming inversion dimers.